Ascent Online Booking Information System Mounts in East Java Based on Android - Cindi Novita Sari Dewi; R Dimas Aditya; Syariful Alim (Fakultas Teknik Universitas Bhayangkara, 2021)
Mountain climbing activities in East Java itself have been carried out by everyone or have been carried out by all groups. For the registration itself is still using manual registration. Because of this, an Android-based online booking application system was created that makes it easier to register for climbers, and also a web application that makes it easier for admins to validate registration. In the web application itself, there is a scheduling method, namely the Shortest Processing Time (SPT) method, so that the admin is easier to filter data that must be validated first. Based on the results of functional testing, it can be seen that, the program runs in accordance with the registration procedure from users using Android to the validation stage from the admin, from the test results it can be stated that the system is feasible to test functionally and error handling testing.